An Analysis of Continuity Intentions of eGovernment Portal Users. Issue 2 (7th February 2016) - Piehler, Robert; Wirtz, Bernd W.; Daiser, Peter
Abstract: This study provides an integrative coherent model of continuity intentions in the context of electronic public service provision drawing from multiple theoretical research streams. Especially the role of citizens' expectations and their determinants for electronic public service delivery is discussed. The research model was empirically examined using a sample from four major German cities and structural equation modelling. The data show that the concepts of this multitheoretical approach are compatible and altogether provide a better understanding of citizens' cognitive processes leading to continued usage behaviour. Both theoretical and practical implications for public administration in general are derived.